La reazione del terapeuta al paziente nell’approccio cognitivo-comportamentale - Bilardi, Giorgia; Testa, Luana (Il sogno della farfalla, 2014)
For a long time, the therapist’s reaction to the patient in the context of cognitive-behavioral psychotherapy has not been part of the cognitivists’ theoretical and clinical research. Between the 1950s and 60s the first exponents of this method dedicated themselves principally to the construction of a pragmatic method which offered itself as an alternative to psychoanalysis. From the 80s some cognitivists of the second generation having understood the limits of the rational method of clinical practice were forced to face the theme of the therapeutic relationship and what happens within it. The authors of this article retrace the history and the development of the cognitivist paradigm, through its interaction with Bowlby’s attachment theory, analyzing its implications in clinical practice which gave rise to the” relational turn” of cognitive-behavioral psychotherapy.